2021
DOI: 10.1038/s41419-021-03718-4
|View full text |Cite
|
Sign up to set email alerts
|

GSTZ1 sensitizes hepatocellular carcinoma cells to sorafenib-induced ferroptosis via inhibition of NRF2/GPX4 axis

Abstract: Increasing evidence supports that ferroptosis plays an important role in tumor growth inhibition. Sorafenib, originally identified as an inhibitor of multiple oncogenic kinases, has been shown to induce ferroptosis in hepatocellular carcinoma (HCC). However, some hepatoma cell lines are less sensitive to sorafenib-induced ferroptotic cell death. Glutathione S-transferase zeta 1 (GSTZ1), an enzyme in the catabolism of phenylalanine, suppresses the expression of the master regulator of cellular redox homeostasis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(132 citation statements)
references
References 43 publications
(40 reference statements)
9
123
0
Order By: Relevance
“…Increasing evidence has also shown that NRF2 can improve the resistance of cancer cells to chemotherapeutic drugs [ 7 , 24 ]. In HCC, it's confirmed that NRF2 is upregulated in tumor tissues, and transcriptionally activates the ferroptosis-related genes such as HO-1, FTH1, and NQO1, which is associated with malignancy and a poor prognosis [ 7 , 39 , 40 ]. Therefore, inhibition of Keap1-NRF2-ARE signal system may represent an attractive approach for the reversal of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has also shown that NRF2 can improve the resistance of cancer cells to chemotherapeutic drugs [ 7 , 24 ]. In HCC, it's confirmed that NRF2 is upregulated in tumor tissues, and transcriptionally activates the ferroptosis-related genes such as HO-1, FTH1, and NQO1, which is associated with malignancy and a poor prognosis [ 7 , 39 , 40 ]. Therefore, inhibition of Keap1-NRF2-ARE signal system may represent an attractive approach for the reversal of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a lack of GSTZ1 can lead to the accumulation of the metabolite succinyl lactone, which activates the NRF2 signaling pathway. [103][104][105] Wang et al 106 found that the depletion of GSTZ1 potentiated the NRF2 pathway and elevated the level of GPX4, thus inhibiting sorafenib-induced ferroptosis. Louandre et al 107 found that retinoblastoma mediates ferroptosis and kills HCC cells by participating in the toxic effects of sorafenib on HCC cells.…”
Section: Ferroptosis In Hcc Treatmentmentioning
confidence: 99%
“…The ability to induce HCC as a late event of CCl 4 induction was used in mice (16% in corn oil, 3x/week/8 weeks) to evaluate the treatment of Sorafenib+ MAPK/ERK pathway inhibitors [ 396 ]. On the other hand, studies also associate the carcinogenic action of DEN with the fibro-cirrhotic capacity of CCl 4 in the chemo [ 397 ] and immunotherapeutic tests [ 398 ]. TAA has also been used in preclinical tests in mice (200 mg/Kg ip or 200 mg/L in drinking water) associated or not with syngeneic and xenographic models, enabling the evaluation of drugs with known or promising potential, chemo or immunotherapy [ 386 , 388 , 399 ].…”
Section: Therapeutic Relevance Of the Hcc Modelsmentioning
confidence: 99%
“…Genetic engineering enabled the creation of transgenic animals with structural and metabolic alterations totally directed to the specificity of the questions formulated for the object of study. In the preclinical researches of HCC, these animals can be inserted in different models, directing the results to a specific signaling pathway both in the testing of new drugs [ 386 , 388 , 396 , 397 ] and in new therapies [ 388 , 389 , 390 , 398 ].…”
Section: Therapeutic Relevance Of the Hcc Modelsmentioning
confidence: 99%
See 1 more Smart Citation